2021
DOI: 10.1111/1462-2920.15401
|View full text |Cite
|
Sign up to set email alerts
|

Population structure of Erysiphe necator on domesticated and wild vines in the Middle East raises questions on the origin of the grapevine powdery mildew pathogen

Abstract: Plant pathogens usually originate and diversify in geographical regions where hosts and pathogens coevolve. Erysiphe necator, the causal agent of grape powdery mildew, is a destructive pathogen of grapevines worldwide. Although Eastern US is considered the centre of origin and diversity of E. necator, previous reports on resistant native wild and domesticated Asian grapevines suggest Asia as another possible origin of the pathogen. By using multi-locus sequencing, microsatellites and a novel application of amp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 84 publications
1
25
0
Order By: Relevance
“…[18, 19,24,50], with the co-evolution theory. However, the Gur et al [57] suggestion is in contrast to common notions on E. necator origin and centres of differentiation [e.g. 53] and a more indepth study would be necessary to con rm their new proposals.…”
Section: Origin Of the Resistance To E Necator In The Caucasian Grapevinesmentioning
confidence: 89%
See 1 more Smart Citation
“…[18, 19,24,50], with the co-evolution theory. However, the Gur et al [57] suggestion is in contrast to common notions on E. necator origin and centres of differentiation [e.g. 53] and a more indepth study would be necessary to con rm their new proposals.…”
Section: Origin Of the Resistance To E Necator In The Caucasian Grapevinesmentioning
confidence: 89%
“…Anyway, Gur et al [57] recently identi ed an E. necator strain in Israel genetically differentiated from those characterized in Europe and North America, proposing a non-American origin for it and possibly an Asian one. This hypothesis could explain the presence of resistance to E. necator in V. vinifera, and also in other Asian Vitis spp.…”
Section: Origin Of the Resistance To E Necator In The Caucasian Grapevinesmentioning
confidence: 99%
“…An isolate of E. necator , obtained from an infected vineyard in the Golan region, Israel (isolate 146, [ 102 ]), was maintained on detached young leaves of V. vinifera cv. Cabernet Sauvignon in a growth chamber at 23 °C, 14-h light photoperiod under fluorescent light of 100 µmole·m −2 ·s −1 .…”
Section: Methodsmentioning
confidence: 99%
“…Conidia of E. necator from 10-days old colonies (isolate 146, [ 102 ]) grown on cv. Cabernet Sauvignon detached leaves were gently brushed above 9-cm petri dishes containing 2% water agar (WA) amended with 1% Top KP+ (containing 0.1, 5, and 3.3 g/L N:P:K respectively), 1% Top KP+ plus 0.1% Nanovatz (containing 0.102 and 0.005 g/L Zn and B respectively), 1% Top KP+ plus 0.25% TruPhos (containing 0.125, 0.45, and 0.05 g/L N:P:K respectively, and 0.02, 0.0025, 0.0125, 0.00125, 0.0025, 0.0025, 0.00125, and 0.00125 g/L Zn, B, Mg, Co, Cu, Fe, Mn, and Mo respectively), 1% Top KP+ plus 0.1% Nanovatz plus 0.025% Triton, 1% Top KP+ plus 0.25% TruPhos plus 0.025% Triton, or only 0.025% Triton.…”
Section: Methodsmentioning
confidence: 99%
“…The practice of viticulture developed in the Middle East in 8000 BC through the cultivation of wild grapes (Gur et al 2021), later the grape variety Vitis vinifera was found, which originated in Europe and till now more than ten thousand white and red grapes varieties were recognized throughout the world (Lumbreras 2003). The development of grapevine plants starts from the shoots (a portion of stems) and after the fourth year, the crop starts giving a constant annual production of grapes, which can ensure their use for industrialization in winemaking (Gattullo et al 2020).…”
Section: Introductionmentioning
confidence: 99%